What Would Humboldt Say: A Case of General Bildung in Vocational Education? - Ruhi Tyson (European Research Network Vocational Education and Training (VETNET), 2016)
A classic philosopher in the Bildung tradition, Humboldt argued that general Bildung was the opposite of specialist training (vocational education). This has been a matter of contention and the aim here is to revisit the issue through an empirical case study. In the vocational education biography of craft master Wolfgang B. he speaks about aspects of his education that have much in common with Humboldt's ideal of general Bildung but transposed into the context of vocational education and training (VET). The concept of vocationalism (Beruflichkeit) provides context to the present argument which is that the contrast Humboldt made is relevant but not in the sense of there being two categories of education (general and vocational) but rather two expressions of pedagogy: one expansive and one exclusive. Furthermore, there are two versions of general or expansive Bildung present in the case. The conclusions are that empirical studies of vocational Bildung expand on the concept of Bildung, increase our understanding of how VET contains affordances of Bildung and of the curriculum-patterns related to this.